Lessons from European Union Policies for Regional Development - Shankar, Raja; Shah, Anwar (2012)
Regional disparities present an ever present development challenge in most countries, especially those with large geographic areas under their jurisdiction. A neglect of these inequities may create the potential for disunity and, in extreme cases, for disintegration. In view of this, most countries actively pursue policies with a view to helping lagging regions catch up with faster growing regions. These policies have at best a mixed record of success. It is therefore useful to discern what type of policies work and why? In this context learning from the experience of the European Union (EU) may be particularly instructive as, over the years, it has provided significant support to assist poorer regions achieve convergence with the richer regions. This paper reviews the impact of EU policies for regional development to draw lessons of interest to other countries pursuing similar goals. The paper concludes that policies that serve to create an internal common market by creating a level playing field that enables poorer regions to integrate with the broader national and global economies have the best potential to advance regional income convergence. In this context, removal of barriers to trade and factor mobility and providing enhanced access to information and technology to the lagging regions should be main policy priorities for regional development.